The Belt and Road as method: Geopolitics, technopolitics and power through an infrastructure lens. (26th October 2021) - Oakes, Tim
Abstract: Although infrastructures may be material manifestations of state territorial power, the political effects of infrastructures are seldom straightforward. And yet, many accounts of the Belt and Road Initiative (BRI) assume a relatively conventional approach to politics, and to political power. Geopolitical intentionality and top‐down policy and strategic planning tend to be emphasised over project‐level analyses. In response to what might be viewed as an invented BRI geopolitics, this essay suggests a more technopolitical framing of the Belt and Road and seeks to apply an infrastructural analytic to the question of how political power is realised or frustrated, enhanced or diverted, by the distributed and relational nature of infrastructure projects. It argues that our understanding of the socio‐technical complexities of infrastructure is poorly served by viewing them through a conventional geopolitical lens. Instead, it seeks to lay out a research agenda and analytical framework for addressing the questions of how infrastructure projects grow and evolve, how they are embedded within the social‐political‐cultural contexts in which they develop and how they produce political effects that at times align with broader‐scale geopolitical agendas and at other times do not.